Experimental Study on Energy Dissipation of Saturated Mudstone in Coal Mine under Impact Loading. (17th March 2022) - Guo, Liangjie; Wang, Yongyu
Abstract : The influence of blasting energy on blasting fragmentation and damage of reserved rock is important for safety and schedule of drill-blasting construction in coal mine. This study is aimed at investigating the dynamic mechanical properties of mudstone in coal mine using the energy characterization method, and their quantitative relation formula was also developed. The impact compression experiments of mudstone in Huainan mining area were conducted to study the saturated mudstone dynamic mechanism, crack properties, and energy dissipation law using the diameter 50 mm split Hopkinson pressure bar (SHPB). The results show that under the back-and-forth reflection of the stress wave, the saturated mudstone specimens are characterized by circumferential failure and axial splitting damage, which appear in the rock grain interface. By energy analysis, the energy dissipation per volume (EDV), energy dissipation per mass (EDM), and absorption impedance energy ratio (AIER) are used to represent the energy dissipation characteristic of mudstone. And the AIER is the best index. Additionally, there is the quadratic function relationship between three indexes and average strain ratio, showing the dependence of the strain ratio.